Developing and Using a Toolkit for Cultivating Compassion in Healthcare: An Appreciative Inquiry Approach - Ramage, Charlotte; Curtis, Kathy; Glynn, Angela; Montgomery, Julia; Hoover, Elona; Leng, Jane; Martin, Claire; Theodosius, Catherine; Gallagher, Ann (International Journal of Practice-based Learning in Health and Social Care, 2017)
This article describes the process of developing and evaluating a ‘cultivating compassionate care’ toolkit of evidence-based training resources designed to be cascaded through a ‘train-the-trainer’ approach in three healthcare organisations in Southern England. The purpose of the project was to develop an awareness of compassion, and to investigate how compassion can be recognised, developed, and sustained within the healthcare workforce. The study was based on appreciative inquiry and a train-the-trainer model, using focus groups to generate evidence-based training tools designed with the staff in the participating organisations. Questionnaires evaluated the first wave of Cultivating Compassion workshops delivered by trainers, while semi-structured interviews and focus groups evaluated the experiences of those using the toolkit. The findings demonstrated that a cultivating compassion toolkit, co-created with the healthcare workforce, can develop confidence in engaging in discourse on the meaning of compassionate care, and provoke a focus on self-compassion and compassion towards colleagues. Thematic analysis of interviews and focus group data with participants involved in cascading the toolkit activities revealed the value and usability of the toolkit resource, and the leadership factors influencing its implementation. We conclude that cultivating compassionate practices requires leadership to clearly articulate their values and vision for compassion, ensuring these are clearly supported and integrated throughout the organisation as part of changing culture and practices to support compassionate care. The limitation of the study was that we were unable, due to the project timeline, to measure impact of the project on patients, their families, and carers.